Hepatocellular carcinoma radiation segmentectomy treatment intensification prior to liver transplantation increases rates of complete pathologic necrosis: an explant analysis of 75 tumors. - Montazeri, S. Ali; De la Garza-Ramos, Cynthia; Lewis, Andrew R.; Lewis, Jason T.; LeGout, Jordan D.; Sella, David M.; Paz-Fumagalli, Ricardo; Devcic, Zlatko; Ritchie, Charles A.; Frey, Gregory T.; Vidal, Lucas; Croome, Kristopher P.; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2022)
Purpose: To verify the correlation between yttrium-90 glass microsphere radiation segmentectomy treatment intensification of hepatocellular carcinoma (HCC) and complete pathologic necrosis (CPN) at liver transplantation. Methods: A retrospective, single center, analysis of patients with HCC who received radiation segmentectomy prior to liver transplantation from 2016 to 2021 was performed. The tumor treatment intensification cohort (n = 38) was prescribed radiation segmentectomy as per response recommendations identified in a previously published baseline cohort study (n = 37). Treatment intensification and baseline cohort treatment parameters were compared for rates of CPN. Both cohorts were then combined for an overall analysis of treatment parameter correlation with CPN. Results: Sixty-three patients with a combined 75 tumors were analyzed. Specific activity, dose, and treatment activity were significantly higher in the treatment intensification cohort (all p < 0.01), while particles per cubic centimeter of treated liver were not. CPN was achieved in 76% (n = 29) of tumors in the treatment intensification cohort compared to 49% (n = 18) in the baseline cohort (p = 0.013). The combined cohort CPN rate was 63% (n = 47). ROC analysis showed that specific activity ≥ 327 Bq (AUC 0.75, p < 0.001), dose ≥ 446 Gy (AUC 0.69, p = 0.005), and treatment activity ≥ 2.55 Gbq (AUC 0.71, p = 0.002) were predictive of CPN. Multivariate logistic regression demonstrated that a specific activity ≥ 327 Bq was the sole independent predictor of CPN (p = 0.013). Conclusion: Radiation segmentectomy treatment intensification for patients with HCC prior to liver transplantation increases rates of CPN. While dose strongly correlated with pathologic response, specific activity was the most significant independent radiation segmentectomy treatment parameter associated with CPN.